Memory device based on two-dimensional ferromagnetic intrinsic temperature-controlled magnetization characteristics and preparation method
By utilizing the temperature control mechanism of the ion gel gate dielectric layer, a non-volatile, programmable magnetic state writing at room temperature was achieved through a memory device based on two-dimensional ferromagnetic materials. This solves the problems of device complexity and high power consumption in existing technologies and provides a new path for high-density spin memory.
Patent Information
- Application Number
- CN202511860798.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-11
- Publication Date
- 2026-02-03
- Estimated Expiration
- 2045-12-11
AI Technical Summary
Existing technologies face challenges in achieving efficient magnetic storage using two-dimensional magnetic materials, especially in achieving non-volatile, programmable magnetic state writing at room temperature. Furthermore, existing gate voltage control techniques are complex, increasing the difficulty of device fabrication and power consumption.
A memory device based on two-dimensional ferromagnetic materials is adopted. An ion gel gate dielectric layer composed of ionic liquid and polymer is used to achieve non-volatile programming by gate voltage above the carrier type transition temperature and magnetic state stability below the transition temperature. The device structure is simplified by combining standard micro-nano fabrication process with two-dimensional material dry transfer technology.
This invention enables programmable, non-volatile, and highly stable magnetic storage without the need for complex stacking structures or external magnetic fields, significantly simplifying the device structure, reducing power consumption, and providing a new path for high-density, interference-resistant spin memories.
Smart Images

Figure CN121310545B_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the field of storage devices, specifically relating to storage devices based on two-dimensional ferromagnetic intrinsic temperature-controlled magnetization characteristics and their fabrication methods. Background Technology
[0002] In recent years, the discovery of two-dimensional magnetic materials has opened up new possibilities for the development of spintronic devices. These materials, with their atomic-level thickness and high sensitivity to the external environment, provide a material basis for developing novel memory devices. Among the many two-dimensional magnetic materials, some exhibit high Curie temperatures and specific magnetic anisotropy, making room-temperature magnetic storage applications possible.
[0003] In the field of magnetic control technology, gate voltage modulation is one of the most important control methods. By applying a gate voltage, the carrier concentration and electronic structure of a material can be changed, thereby affecting its magnetism. Traditional solid-state gate technology has limitations in its controllability, while ionic liquid / ionic gel gate technology, due to its unique interface effect, can achieve more effective magnetic control.
[0004] However, current technologies still face challenges in achieving efficient magnetic storage using two-dimensional magnetic materials. Currently, the main technological approach to achieving high-density magnetic storage involves complex device structure designs, such as integrating multiple magnetic units within a single storage cell, or using magnetic topology for encoding. While this increases storage density, it also increases the difficulty of device fabrication, integration complexity, and power consumption of the control circuitry. Furthermore, existing gate voltage modulation techniques often struggle to achieve non-volatile, programmable magnetic state writing, especially at room temperature. Summary of the Invention
[0005] The technical problem to be solved by this application is to provide a storage device and a preparation method based on the intrinsic temperature-controlled magnetization characteristics of two-dimensional ferromagnetic materials, which can make full use of the intrinsic characteristics of two-dimensional ferromagnetic materials to achieve a simpler structure and better performance.
[0006] In a first aspect, this application provides a storage device based on two-dimensional ferromagnetic intrinsic temperature-controlled magnetization characteristics, comprising:
[0007] Substrate;
[0008] The source electrode and the drain electrode are disposed on the substrate;
[0009] A gate electrode is disposed on the substrate and forms a side gate structure with the source electrode and the drain electrode;
[0010] A channel layer is disposed between the source electrode and the drain electrode, and the channel layer comprises a two-dimensional ferromagnetic material sheet;
[0011] A gate dielectric layer, covering the gate electrode and the entire channel layer, is formed of an ion gel composed of ionic liquid and polymer. When a gate voltage is applied, a nanoscale electric double layer is formed at the interface between the ion gel and the channel layer. Under conditions above the carrier type transition temperature, the magnetic properties of the channel layer can be non-volatilely programmed by the gate voltage; under conditions below the transition temperature, the channel layer exhibits magnetic state stability for the same gate write operation, achieving thermal write protection.
[0012] Optionally, the two-dimensional ferromagnetic material is selected from Fe5GeTe2, Fe3GeTe2, Fe3GaTe2, Ni-doped Fe5GeTe2, Co-doped Fe5GeTe2, or Cr2X2Y, wherein X is Ge or Si, and Y is Te or Se.
[0013] Optionally, the ionic liquid comprises at least one of 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, 1-hexyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, 1-ethyl-3-methylimidazolium tetrafluoroborate, and 1-ethyl acetate-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt.
[0014] Optionally, the polymer includes at least one selected from polyvinylidene fluoride-hexafluoropropylene, polyvinylidene fluoride, perfluoroethylene propylene, polytetrafluoroethylene, polyethylene oxide, polyethylene glycol, and polyacrylonitrile.
[0015] Optionally, the substrate is a Si / SiO2 wafer, sapphire, quartz, or glass.
[0016] Optionally, the source electrode, drain electrode, and gate electrode are made of Cr / Au, Ti / Au, Pd / Au, Pt / Au, or Ni / Au metal composite materials, wherein the thickness of the Au layer is 10-30 nm.
[0017] Optionally, the thickness of the two-dimensional ferromagnetic material sheet is 10-50 nm.
[0018] Optionally, the thickness of the gate dielectric layer is 100-500 nm.
[0019] Optionally, the weight ratio of ionic liquid to polymer in the ionic gel is 3 to 5:1.
[0020] Optionally, the capacitance of the nano-electric double layer formed by the gate dielectric layer is μF / cm. 2 Level, can induce 10 14 -10 15 cm -2 Surface carrier concentration.
[0021] Secondly, this application provides a method for fabricating a storage device based on two-dimensional ferromagnetic intrinsic temperature-controlled magnetization characteristics, comprising the following steps:
[0022] On the substrate, source electrodes, drain electrodes, and gate electrodes are formed through ultraviolet lithography, metal evaporation, and lift-off processes;
[0023] Two-dimensional ferromagnetic material sheets are obtained by mechanical peeling and transferred between the source and drain electrodes on the substrate to form a channel layer.
[0024] Ionic gels were prepared by dissolving ionic liquids and polymers in a solvent and then spin-coating them.
[0025] The prepared ion gel is coated onto the gate electrode and all channel layers to form the gate dielectric layer.
[0026] Optionally, the formation of the source electrode, drain electrode, and gate electrode includes the following steps: spin coating of photoresist, electron beam exposure, development, evaporation of a metal layer, and stripping.
[0027] Optionally, the mechanical stripping method includes: obtaining a two-dimensional ferromagnetic material sheet from a bulk single crystal using a polymer stripping medium with controllable adhesion properties, and then aligning the polymer stripping medium with the two-dimensional ferromagnetic material sheet with a prefabricated electrode on a substrate, and separating the polymer stripping medium by slow contact and heating or dissolving.
[0028] Optionally, the polymer stripping medium is selected from at least one of polydimethylsiloxane, polycarbonate, polymethyl methacrylate, ethylene-vinyl acetate copolymer, polydimethylsiloxane modified material, polyolefin elastomer, polyvinyl alcohol, and polyethylene oxide.
[0029] The beneficial effects of this application are:
[0030] The first aspect of this application provides a memory device based on the intrinsic temperature-controlled magnetization characteristics of two-dimensional ferromagnetic materials. This device utilizes a coupling mechanism between the inherent temperature-dependent carrier type transition characteristics of specific two-dimensional ferromagnetic materials and a strong electrochemical control mechanism induced by an ion-gel gate. When the operating temperature is higher than the material's carrier type transition temperature, the channel exhibits a hole-dominated conductivity state, which facilitates interfacial redox reactions under positive gate voltage, thereby non-volatilely controlling the magnetization intensity and enabling the writing of multi-state information. Conversely, when the temperature is lower than this transition point, the channel becomes electron-dominated, thermodynamically or kinetically suppressing the electrochemical writing process under the same gate voltage, thus maintaining magnetic stability and forming a "thermally controlled write protection" mechanism. This two-dimensional ferromagnetic memory device eliminates the need for complex stacking structures or external magnetic fields, achieving programmable, non-volatile, and highly stable magnetic storage functions solely through temperature and gate voltage coordination. This significantly simplifies the device structure, reduces power consumption, and provides a new path for high-density, interference-resistant spin memories.
[0031] The second aspect of this application provides a method for fabricating a memory device based on the intrinsic temperature-controlled magnetization characteristics of two-dimensional ferromagnetic materials. By integrating standard micro / nano fabrication processes with two-dimensional material dry transfer technology, and combining this with a low-temperature solution preparation process for high-capacitance ion-gel gate media, a novel and structurally simple temperature-controlled magnetic memory device is constructed. This method achieves non-volatile, programmable magnetic storage with thermal write protection without the need for complex multilayer stacking or external magnetic fields, significantly reducing device structural complexity and power consumption. It is also compatible with existing planar processes, providing a feasible path for the practical application of high-density, low-power spintronic memories. Attached Figure Description
[0032] Figure 1 This is a schematic diagram of the structure of the storage device provided in the embodiments of this application;
[0033] Figure 2 A connection diagram of an electrical testing system for storage devices provided in an embodiment of this application;
[0034] Figure 3 The changes in Hall resistance curves of the storage device provided in the embodiments of this application when different positive gate voltages are applied at 200K;
[0035] Figure 4 (a) A comparison graph of Hall resistance curves measured by applying a 1V gate voltage and not applying a gate voltage at a temperature of 200K for the memory device provided in the embodiments of this application; (b) A comparison graph of Hall resistance curves measured by applying a 1V gate voltage and not applying a gate voltage at a temperature of 150K; (c) A comparison graph of Hall resistance curves measured by applying a 1V gate voltage and not applying a gate voltage at a temperature of 100K; (d) A comparison graph of Hall resistance curves measured by applying a 1V gate voltage and not applying a gate voltage at a temperature of 90K.
[0036] In the figure: 100, memory device; 110, substrate; 120, source electrode; 130, drain electrode; 140, gate electrode; 150, channel layer; 160, gate dielectric layer; 170, Hall voltage measurement terminal; 200, nanovoltmeter; 300, voltage source; 400, current source. Detailed Implementation
[0037] To make the technical problems, technical solutions, and beneficial effects to be solved by this application clearer, the following detailed description is provided in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and are not intended to limit the scope of this application.
[0038] like Figure 1 As shown, in a first aspect, this application provides a storage device based on two-dimensional ferromagnetic intrinsic temperature-controlled magnetization characteristics, comprising:
[0039] Substrate 110;
[0040] The source electrode 120 and the drain electrode 130 are disposed on the substrate 110;
[0041] A gate electrode 140 is disposed on a substrate 110 and forms a side gate structure with a source electrode 120 and a drain electrode 130.
[0042] A channel layer 150 is disposed between the source electrode 120 and the drain electrode 130, and the channel layer 150 includes a two-dimensional ferromagnetic material sheet.
[0043] The gate dielectric layer 160 covers the gate electrode 140 and the entire channel layer 150. It is formed by an ion gel composed of ionic liquid and polymer. When a gate voltage is applied, a nanoscale double layer is formed at the interface between the ion gel and the channel layer 150. Under conditions above the carrier type transition temperature, the magnetic properties of the channel layer 150 can be non-volatilely programmed by the gate voltage. Under conditions below the transition temperature, the channel layer 150 exhibits magnetic state stability for the same gate write operation, thereby achieving thermal write protection.
[0044] The first aspect of this application provides a memory device 100 based on the intrinsic temperature-controlled magnetization characteristics of two-dimensional ferromagnetic materials. This device utilizes a coupling mechanism between the inherent temperature-dependent carrier type transition characteristics of a specific two-dimensional ferromagnetic material and a strong electrochemical control mechanism induced by an ion-gel gate. When the operating temperature is higher than the material's carrier type transition temperature, the channel is hole-dominated, which facilitates interfacial redox reactions under positive gate voltage, thereby non-volatilely controlling the magnetization intensity and enabling the writing of multi-state information. Conversely, when the temperature is lower than this transition point, the channel becomes electron-dominated, thermodynamically or kinetically suppressing the electrochemical writing process under the same gate voltage, thus maintaining magnetic stability and forming a "thermally controlled write protection" mechanism. This two-dimensional ferromagnetic memory device 100 eliminates the need for complex stacking structures or external magnetic fields, achieving programmable, non-volatile, and highly stable magnetic storage functions solely through temperature and gate voltage coordination. This significantly simplifies the device structure, reduces power consumption, and provides a new path for high-density, interference-resistant spin memories.
[0045] In one possible implementation, the two-dimensional ferromagnetic material is selected from Fe5GeTe2, Fe3GeTe2, Fe3GaTe2, Ni-doped Fe5GeTe2, Co-doped Fe5GeTe2, or Cr2X2Y, where X is Ge or Si and Y is Te or Se.
[0046] Specifically, these materials are van der Waals ferromagnets with intrinsic magnetic order and temperature-dependent transport properties. Fe5GeTe2, in particular, and its doped variants exhibit significant carrier type transition behavior (from low-temperature n-type to high-temperature p-type) around 150 K, enabling them to synergize with the strong electric field or electrochemical effects generated by the ion-gel gate: above this transition temperature, the p-type conductivity promotes interfacial oxidation, achieving non-volatile magnetization writing; below this temperature, the n-type surface inhibits this process, automatically entering a write-locked state. Other candidate materials, such as Fe3GeTe2, although having lower Curie temperatures, can have their carrier concentration, magnetic anisotropy, and transition temperature controlled through elemental substitution (e.g., Ga replacing Ge) or transition metal doping (Ni, Co), thus adapting to the temperature-controlled storage mechanism of this invention. This implementation expands the applicability of the device under different operating temperature ranges and performance requirements through flexible selection of material systems and bandgap engineering, while maintaining the advantages of simple structure and strong process compatibility.
[0047] In one possible implementation, the ionic liquid includes at least one of 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide ([EMIM][TFSI]), 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide ([BMIM][TFSI]), 1-hexyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide ([HMIM][TFSI]), 1-ethyl-3-methylimidazolium tetrafluoroborate ([EMIM][BF4]), and 1-ethyl acetate-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt.
[0048] Specifically, these ionic liquids all possess high ionic conductivity, a wide electrochemical window, and low volatility, enabling them to rapidly form a nanoscale electric double layer at the interface of a two-dimensional ferromagnetic channel under gate bias, inducing up to 10 14 -10 15 cm -2 Carrier concentrations on the order of magnitude; including [TFSI] - Anionic liquids (such as [EMIM] and [TFSI]) are particularly advantageous for driving non-volatile magnetization writing in high-temperature regions due to their strong hydrophobicity, high stability, and ability to promote reversible / quasi-irreversible electrochemical reactions. This process is suppressed in low-temperature regions due to the change in carrier type, thus enabling temperature-controlled writing and locking. By adjusting the length of the cationic alkyl chain (e.g., from ethyl to hexyl) or introducing functionalized groups (e.g., ethyl acetate), ion mobility, interfacial wettability, and electrochemical activity can be further modulated to optimize the device's write speed, retention time, and operating temperature window, thereby improving the adjustability and reliability of storage performance.
[0049] In one possible implementation, the polymer includes at least one of polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), polyvinylidene fluoride (PVDF), perfluoroethylene propylene (FEP), polytetrafluoroethylene (PTFE), polyethylene oxide (PEO), polyethylene glycol (PEG), and polyacrylonitrile (PAN).
[0050] Specifically, these polymers primarily function as a support framework and regulate ion migration in ion gel systems. PVDF-HFP and PVDF, due to their high dielectric constant, good film-forming properties, and excellent compatibility with imidazole ionic liquids, can effectively dissolve and immobilize ionic liquids while maintaining over 90% double-layer capacitance, making them ideal choices for high-performance gate control. PEO and PEG, rich in etheroxy groups, can promote lithium-ion or proton conduction, improving doping efficiency in specific electrochemical writing mechanisms. While FEP and PTFE exhibit strong hydrophobicity and excellent chemical stability, their film-forming flexibility is relatively low, making them suitable for encapsulation scenarios with stringent environmental stability requirements. PAN, with its high polarity and thermal stability, can be used to enhance the mechanical strength of the gel. By rationally selecting or combining these polymers, the ionic conductivity, electrochemical window, and interfacial characteristics can be controlled while maintaining the flexibility and processability of the ion gel. This allows for adaptation to the temperature-controlled magnetization response requirements of different two-dimensional ferromagnetic materials, optimizing the device's writing efficiency, non-volatility retention, and cycle stability.
[0051] In one possible implementation, the substrate 110 is not limited to a material selected from Si / SiO2 wafers, sapphire, quartz or glass, wherein the SiO2 layer thickness is 180-400 nm.
[0052] For example, the thickness of the SiO2 layer can be any typical but non-limiting point value or a range between any two points, such as 180nm, 200nm, 250nm, 300nm, 350nm, 400nm, etc. In this case, on the one hand, SiO2, as an insulating layer, can effectively isolate the channel from the conductive silicon substrate 110 and avoid leakage current interference; on the other hand, its thickness is sufficient to provide good surface flatness and optical contrast, which is convenient for subsequent identification and positioning of the two-dimensional ferromagnetic material sheet obtained by mechanical peeling through optical microscopy, while not affecting the electric field coupling efficiency of the side gate electrode 140 due to excessive thickness.
[0053] In one possible implementation, depending on the requirements for contact resistance or work function matching, the materials of the source electrode 120, drain electrode 130, and gate electrode 140 are selected from Cr / Au, Ti / Au, Pd / Au, Pt / Au, or Ni / Au metal composite materials, wherein the thickness of the Cr, Ti, Pd, Pt, or Ni layer is 3-8 nm, and the thickness of the Au layer is 10-30 nm.
[0054] For example, the thickness of the Cr, Ti, Pd, Pt, or Ni layer can be any typical but non-limiting point value or a range between any two points, such as 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, or 8 nm; the thickness of the Au layer can be any typical but non-limiting point value or a range between any two points, such as 10 nm, 15 nm, 20 nm, 25 nm, or 30 nm. In this case, the Cr, Ti, Pd, Pt, or Ni layer serves as an adhesion layer to ensure good adhesion between the metal electrode and the substrate 110; the gold (Au) layer serves as a conductive layer, providing low-resistance contact and ensuring the stability and reliability of the device in electrical transport measurements; it can effectively avoid magnetic interference caused by excessively thick adhesion layers or electromigration problems caused by excessively thin conductive layers, thereby minimizing disturbances to the intrinsic magnetic transport characteristics of the channel while ensuring electrical performance.
[0055] In one possible implementation, the thickness of the two-dimensional ferromagnetic material sheet is 10-50 nm.
[0056] For example, the thickness of a two-dimensional ferromagnetic material sheet can be any typical but not limiting value, such as 10 nm, 20 nm, 30 nm, 40 nm, or 50 nm, or any range between any two values. In this case, the intrinsic long-range ferromagnetic order and perpendicular magnetic anisotropy of the material can be maintained, while fully exhibiting the quantum confinement effect and surface sensitivity in the two-dimensional limit, which is beneficial for efficient carrier control induced by gate electric field or ion gel. At the same time, this thickness range takes into account both material stability and device fabrication: too thin (<10 nm) may lead to structural incompleteness, easy oxidation, or magnetic quenching; too thick (>50 nm) will weaken gate control efficiency and reduce the ability of the interface double layer to modulate the overall magnetism.
[0057] In one possible implementation, the thickness of the gate dielectric layer 160 is 100-500 nm.
[0058] For example, the thickness of the gate dielectric layer 160 can be any typical but non-limiting value such as 100nm, 200nm, 300nm, 400nm, or 500nm, or a range between any two values. In this case, good film uniformity, mechanical flexibility, and electrode coverage can be ensured to avoid short circuits or breakage, while also ensuring that ions migrate quickly to the channel interface after the gate voltage is applied, effectively forming an electric double layer to achieve efficient magnetic control.
[0059] In one possible implementation, the weight ratio of ionic liquid to polymer in the ionic gel is 3 to 5:1.
[0060] For example, the weight ratio of ionic liquid to polymer in ionic gels can be any typical but non-limiting point value or a range between any two points, such as 3:1, 4:1, or 5:1. In this case, both high ionic conductivity and strong gate control capability can be guaranteed, while maintaining good film-forming properties and mechanical stability of the gel. Too low a ratio will weaken the control effect, while too high a ratio will make the gel too fluid and difficult to integrate. Therefore, this range achieves an optimized balance between performance and process.
[0061] In one possible implementation, the capacitance of the nano-electric double layer formed by the gate dielectric layer 160 is μF / cm. 2 Level, can induce 10 14 -10 15 cm -2 The surface carrier concentration is thus significantly modulated, thereby significantly controlling the Fermi level and magnetic state of two-dimensional ferromagnetic materials, providing a physical basis for realizing non-volatile temperature-controlled writing.
[0062] Secondly, this application provides a method for fabricating a storage device 100 based on two-dimensional ferromagnetic intrinsic temperature-controlled magnetization characteristics, comprising the following steps:
[0063] On substrate 110, source electrode 120, drain electrode 130 and gate electrode 140 are formed by ultraviolet lithography, metal evaporation and lift-off processes.
[0064] Two-dimensional ferromagnetic material sheets are obtained by mechanical peeling and transferred between the source electrode 120 and the drain electrode 130 on the substrate 110 to form a channel layer 150.
[0065] Ionic gels were prepared by dissolving ionic liquids and polymers in a solvent and then spin-coating them.
[0066] The prepared ion gel is coated onto the gate electrode 140 and all the channel layers 150 to form the gate dielectric layer 160.
[0067] The second aspect of this application provides a method for fabricating a memory device 100 based on the intrinsic temperature-controlled magnetization characteristics of two-dimensional ferromagnetic materials. By integrating standard micro / nano fabrication processes with two-dimensional material dry transfer technology, and combining this with a low-temperature solution preparation process for a high-capacitance ion-gel gate medium, a novel and structurally simple temperature-controlled magnetic memory device 100 is constructed. This method achieves non-volatile, programmable magnetic storage with thermal write protection without the need for complex multilayer stacking or external magnetic fields, significantly reducing device structural complexity and power consumption. It is also compatible with existing planar processes, providing a feasible path for the practical application of high-density, low-power spintronic memories.
[0068] In one possible implementation, the formation of the source electrode 120, the drain electrode 130, and the gate electrode 140 includes the following steps: spin coating of photoresist, electron beam exposure, development, evaporation of a metal layer, and stripping.
[0069] Specifically, the formation of the source electrode 120, drain electrode 130, and gate electrode 140 includes: spin-coating an electron beam photoresist (such as PMMA) onto a substrate 110, defining the electrode pattern by electron beam exposure, and forming a mask window after development; subsequently, using thermal evaporation or electron beam evaporation to sequentially deposit Cr, Ti, Pd, Pt, or Ni (3-8 nm) as an adhesion layer and Au (10-30 nm) as a conductive layer; and finally, removing excess photoresist and the metal covering it by solvent immersion lift-off, retaining the desired electrode structure.
[0070] In one possible implementation, the mechanical exfoliation method includes: using a polymer exfoliation medium with controllable adhesion properties to peel a thin sheet from a bulk two-dimensional ferromagnetic single crystal; subsequently, precisely aligning the polymer medium carrying the sheet with the pre-prepared source / drain electrode 130 region on the substrate 110 via a three-dimensional transfer stage; bringing the sheet into contact with the electrode through slow pressing, and separating the polymer exfoliation medium from the two-dimensional ferromagnetic material by annealing at 100-120°C or selectively dissolving the polymer, thereby transferring the sheet non-destructively and cleanly to the target location to form the channel layer 150. This method avoids contamination or material degradation caused by wet etching, is suitable for two-dimensional magnetic materials that are air-sensitive or easily soluble in organic solvents, and ensures device interface quality and intrinsic magnetic transport characteristics.
[0071] In one possible implementation, the polymer stripping medium is selected from at least one of polydimethylsiloxane (PDMS), polycarbonate (PC), polymethyl methacrylate (PMMA), ethylene-vinyl acetate copolymer (EVA), polydimethylsiloxane modified materials, polyolefin elastomers (such as SEBS), polyvinyl alcohol (PVA), and polyethylene oxide (PEO).
[0072] Specifically, these materials each possess different adhesion properties, thermal responsiveness, or solubility. PDMS and EVA are suitable for dry thermal release transfer, PMMA and PC are commonly used for wet-assisted transfer, while PVA and PEO can achieve residue-free peeling through water solubility. Modified PDMS or polyolefin elastomers can further modulate the interfacial adhesion force to adapt to the peeling energy of different two-dimensional ferromagnetic materials. By selecting appropriate peeling media based on material stability, process compatibility, and cleanliness requirements, high-precision, low-damage channel layer 150 integration can be achieved while ensuring the integrity of the two-dimensional ferromagnetic material sheet, providing crucial support for the reliable fabrication of temperature-controlled magnetic storage devices 100.
[0073] In one possible implementation, the solvent used in the ionogel preparation process is selected from at least one of acetone, acetonitrile, N,N-dimethylformamide, N,N-dimethylacetamide, tetrahydrofuran, ethanol, and isopropanol.
[0074] Specifically, these solvents can be flexibly combined according to the solubility characteristics of the selected polymer and ionic liquid. By rationally selecting the type or combination of solvents, the kinetics of spin coating can be controlled while ensuring the homogeneity of the solution, so as to obtain an ion gel dielectric layer with no pinholes, high ionic conductivity and good mechanical properties.
[0075] In order to enable those skilled in the art to clearly understand the above-described implementation details and operations of this application, and to demonstrate the significant improvement in performance of the storage device 100 and its preparation method based on the intrinsic temperature-controlled magnetization characteristics of two-dimensional ferromagnetic in this application, the above technical solutions are illustrated below through multiple embodiments.
[0076] Example 1
[0077] The specific steps for manufacturing the storage device 100 are as follows:
[0078] (1) Preparation of substrate 110: A high-resistivity silicon wafer with a thermally oxidized SiO2 layer is selected as substrate 110, wherein the SiO2 thickness is 300nm, and the surface is cleaned by standard RCA and dried by nitrogen before use.
[0079] (2) Electrode patterning and fabrication: A layer of positive photoresist was spin-coated on the Si / SiO2 substrate 110. The source electrode 120, drain electrode 130 and side gate electrode 140 of the Hall bar structure were defined by ultraviolet lithography, as well as two Hall voltage measurement terminals 170 for subsequent testing. Subsequently, 5 nm Cr (as an adhesion layer) and 20 nm Au (as a conductive layer) were deposited sequentially by electron beam evaporation. Finally, the stripping process was completed by immersion in acetone to form the Cr / Au composite source electrode 120, drain electrode 130 and side gate electrode 140.
[0080] (3) Transfer of channel layer 150: In a high-purity nitrogen glove box (O2 and H2O content are both less than 1 ppm), polydimethylsiloxane (PDMS) is used to mechanically peel off the thin film from the Fe5GeTe2 bulk single crystal; using a three-dimensional micromanipulation transfer platform, the PDMS with the Fe5GeTe2 thin film is precisely aligned with the source / drain electrode 130 region already prepared on the substrate 110; the film is slowly pressed down to make contact with the electrode, and the film is kept at 120 °C for 3 minutes to enhance the interface contact; then the PDMS is slowly lifted to achieve dry non-destructive transfer and obtain the Fe5GeTe2 channel layer 150 located between the source and drain electrodes 130.
[0081] (4) Preparation of gate dielectric layer 160: Polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide ([EMIM][TFSI]) ionic liquid and acetone are mixed in a weight ratio of 1:4:7 and mechanically stirred until a clear ion gel solution is formed; the solution is drop-coated onto a clean silicon wafer and a flexible ion gel film is prepared by a two-step spin coating process (first 600 rpm / 6s, then 1500 rpm / 30s); after the solvent evaporates naturally, the gel film is peeled off from the silicon wafer, cut into a suitable size, and attached to cover the Fe5GeTe2 channel region and gate voltage electrode of the device to form gate dielectric layer 160.
[0082] The final memory device 100 structure, from bottom to top, consists of: a Si / SiO2 substrate 110, Cr / Au source / drain / gate electrodes 140, a Fe5GeTe2 two-dimensional ferromagnetic channel layer 150, and a [EMIM][TFSI] / PVDF-HFP ion-gel gate dielectric. This device can achieve non-volatile writing to the magnetized state by applying a positive gate voltage at temperatures above approximately 150 K, and automatically enters a write-locked state below this temperature, exhibiting excellent temperature-controlled magnetic storage capabilities.
[0083] The storage device 100 obtained in Embodiment 1 was tested, as follows:
[0084] Test method:
[0085] By connecting external instruments and circuits to an existing Power Property Measurement System (PPMS), a platform for magnetoelectric transport measurements was built. For electrical measurements, we plan to use the following source meters: a Keithley 2400 source meter and a Keithley 2182 nanovoltmeter. The main focus will be on testing and analyzing magnetoresistive and Hall effect measurements.
[0086] like Figure 2 The electrical measurement system connection diagram is shown, where B represents the magnetic field, and "⊙B" indicates the direction in which the magnetic field is applied. A Keithley 2400 source meter is used as the current source 400, applying current to create a magnetic field in the vertical plane. Two nanovoltmeters are used to simultaneously measure the long-axis magnetoresistance and anomalous Hall magnetoresistance. Another Keithley 2400 source meter is used as the voltage source 300, applying a grid voltage. Test procedure: (i) A fixed DC grid voltage (V) is applied at 270K. g (ii) Maintain V for 30 minutes to ensure that the ions are mobile and move sufficiently to the interface to reach equilibrium. g The temperature was lowered to 200 K at a rate of 3 K / min, at which point the ion mobility in the ionogel decreased sharply, the ions were frozen, and then the V... gDue to the quasi-permanent electrochemical effect occurring at the interface under higher temperatures (270K) and positive gate voltages, the carrier concentration modulation effect fixed by this effect is non-volatilely maintained over the timescale of low-temperature measurements. The Hall resistance is measured at a fixed temperature of ±1.5T with a current of 0.05mA. To change V... g If the device is damaged, it needs to be reheated to 270K and steps (i) and (ii) repeated. After each heating and cooling cycle, it needs to be stabilized for 20 minutes to ensure that the device has dropped to the specified temperature.
[0087] (iii) Erasure step (optional): If it is necessary to erase the written state, it is speculated that the device can be heated to 270K, a sufficiently large negative gate voltage (e.g. -3V, the specific threshold needs to be determined experimentally) can be applied and held for 30 minutes to drive the reverse electrochemical effect at the state interface and restore the device to the initial magnetization state.
[0088] Experimental phenomena:
[0089] (1) Phenomenon 1: "Write" mode in the high temperature zone (T≥150K)
[0090] When T≥150K, the internal conductivity of Fe5GeTe2 is dominated by holes. Applying a positive gate voltage can increase the saturation magnetization (M) of Fe5GeTe2. s Effective and deterministic regulation should be implemented. For example... Figure 3 As shown, at 200K temperature, with V g As V increases from 0V, the saturation anomalous Hall resistance (with M) increases. s (Proportional to) a significant increase. Choosing different V values... g Size (e.g., 1.5V, 2.5V, 5V), can be M s Precise setting to multiple distinct deterministic states enables non-volatile state writing. This indicates that the device is in a programmable, writable state in the high-temperature region.
[0091] It is worth noting that once a larger V is passed g A relatively high M was set s State, apply a smaller V g It is unrecoverable, non-volatile, and exhibits unidirectional threshold write characteristics. This effective control occurs at a relatively high temperature (200K in experiments), offering significant practical advantages compared to many two-dimensional magnetic systems that only operate at extremely low temperatures. By employing finer gate voltage steps, more deterministic states that can be stably distinguished can be achieved, thus providing a feasible path to increasing storage density.
[0092] (2) Phenomenon 2: "Read-only / write protection" mode in the low temperature zone (T<150K)
[0093] When T < 150 K, Fe5GeTe2 is electron-dominated in its conductivity, and applying the exact same positive gate voltage has almost no effect on the material's magnetism. For example... Figure 4 As shown, when V g At 1V, a significant increase in saturation magnetization can be observed at temperatures of 200K and 150K, but the Hall curves at temperatures of 100K and 90K almost completely overlap with those at which no gate voltage is applied. This indicates that in the low-temperature region, the device enters a read-only or write-protected state that is "immune" to electrical writes.
[0094] The Fe5GeTe2-based memory device 100 fabricated in this embodiment cleverly utilizes the synergistic effect between the intrinsic carrier type temperature transition characteristics of the material and the electrochemical regulation of the ion gel gate to achieve a unique temperature-controlled dual-mode function: In the high-temperature region (T ≥ 150 K), the material is in a hole-dominated (P-type) state. This P-type chemical environment allows and promotes the non-volatile redox reaction of the ion gel under a positive gate voltage. The device is in a programmable state, and by applying different amplitudes of positive gate voltage (V... g This technology allows for the non-volatile and precise setting of the device's saturation magnetization to multiple deterministic states for information storage. In the low-temperature region (T < 150 K), the material becomes electron-dominant (N-type), effectively suppressing electrochemical writing reactions and making the device "immune" to external gate voltages, entering a highly stable read-only / protected mode. This mechanism not only provides the device with physical data tamper-proof capabilities—the state is "frozen" after writing and cooling, preventing accidental overwriting during reading or standby—but also allows for erasure and rewriting by applying a negative gate voltage at high temperatures, restoring the device to its initial state, thus achieving reconfigurable read-only storage. It is particularly suitable for "cold storage" scenarios with stringent requirements for data integrity and long-term security, such as data centers, judicial evidence storage, and scientific research archiving. It can achieve permanent, interference-resistant information sealing in the liquid nitrogen temperature range (77 K) or conventional low-temperature environments, combining high security, low power consumption, and a simple structure.
[0095] Those skilled in the art should understand that the discussion of any of the above embodiments is merely exemplary and is not intended to imply that the scope of protection of this application is limited to these examples; within the framework of this application, the technical features of the above embodiments or different embodiments can also be combined, the steps can be implemented in any order, and there are many other variations of different aspects of one or more embodiments of this application as described above, which are not provided in detail for the sake of brevity.
[0096] One or more embodiments in this application are intended to cover all such substitutions, modifications, and variations that fall within the broad scope of this application. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of one or more embodiments in this application should be included within the protection scope of this application.
Claims
1. A storage device based on two-dimensional ferromagnetic intrinsic temperature-controlled magnetization characteristics, characterized in that, include: Substrate (110); A source electrode (120) and a drain electrode (130) are disposed on the substrate (110); A gate electrode (140) is disposed on the substrate (110) and forms a side gate structure with the source electrode (120) and the drain electrode (130); A channel layer (150) is disposed between the source electrode (120) and the drain electrode (130), and the channel layer (150) comprises a two-dimensional ferromagnetic material sheet; A gate dielectric layer (160) covers the gate electrode (140) and all the channel layers (150), and is formed by an ionic gel composed of an ionic liquid and a polymer. When a gate voltage is applied, a nanoscale double layer is formed at the interface between the ionic gel and the channel layer (150). Under conditions higher than the carrier type transition temperature, the magnetism of the channel layer (150) can be non-volatilely programmed by the gate voltage. At temperatures below the transition temperature, the channel layer (150) exhibits magnetic state stability for the same gate write operation, thus achieving thermal write protection.
2. The storage device based on the intrinsic temperature-controlled magnetization characteristics of two-dimensional ferromagnetism according to claim 1, characterized in that, The two-dimensional ferromagnetic material is selected from Fe5GeTe2, Fe3GeTe2, Fe3GaTe2, Ni-doped Fe5GeTe2, Co-doped Fe5GeTe2 or Cr2X2Y, wherein X is Ge or Si and Y is Te or Se.
3. The storage device based on the intrinsic temperature-controlled magnetization characteristics of two-dimensional ferromagnetism according to claim 1, characterized in that, The ionic liquid comprises at least one of 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, 1-hexyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, 1-ethyl-3-methylimidazolium tetrafluoroborate, and 1-ethyl acetate-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt.
4. The storage device based on the intrinsic temperature-controlled magnetization characteristics of two-dimensional ferromagnetism according to claim 1, characterized in that, The polymer includes at least one of polyvinylidene fluoride-hexafluoropropylene, polyvinylidene fluoride, perfluoroethylene propylene, polytetrafluoroethylene, polyethylene oxide, polyethylene glycol, and polyacrylonitrile.
5. The storage device based on the intrinsic temperature-controlled magnetization characteristics of two-dimensional ferromagnetism according to claim 1, characterized in that, The substrate (110) is made of Si / SiO2 wafer, sapphire, quartz or glass; And / or, the source electrode (120), drain electrode (130) and gate electrode (140) are made of Cr / Au, Ti / Au, Pd / Au, Pt / Au or Ni / Au metal composite materials, wherein the thickness of the Au layer is 10-30nm; And / or, the thickness of the two-dimensional ferromagnetic material sheet is 10-50 nm.
6. The storage device based on the intrinsic temperature-controlled magnetization characteristics of two-dimensional ferromagnetism according to claim 1, characterized in that, The thickness of the gate dielectric layer (160) is 100-500 nm; And / or, the weight ratio of ionic liquid to polymer in the ionic gel is 3~5:
1.
7. The storage device based on the intrinsic temperature-controlled magnetization characteristics of two-dimensional ferromagnetism according to claim 1, characterized in that, The capacitance of the nano-double layer formed by the gate dielectric layer (160) is μF / cm. 2 Level, can induce 10 14 -10 15 cm -2 Surface carrier concentration.
8. A method for fabricating a storage device based on the intrinsic temperature-controlled magnetization characteristics of two-dimensional ferromagnetism as described in any one of claims 1-7, characterized in that, Includes the following steps: On the substrate (110), a source electrode (120), a drain electrode (130) and a gate electrode (140) are formed by ultraviolet lithography, metal evaporation and lift-off processes. Two-dimensional ferromagnetic material sheets are obtained by mechanical peeling and transferred between the source electrode (120) and the drain electrode (130) on the substrate (110) to form a channel layer (150). Ionic gels were prepared by dissolving ionic liquids and polymers in a solvent and then spin-coating them. The prepared ion gel is coated onto the gate electrode (140) and all the channel layers (150) to form the gate dielectric layer (160).
9. The method for fabricating a storage device based on the intrinsic temperature-controlled magnetization characteristics of two-dimensional ferromagnetism according to claim 8, characterized in that, The formation of the source electrode (120), drain electrode (130) and gate electrode (140) includes the following steps: spin coating of photoresist, electron beam exposure, development, evaporation of metal layer, and stripping. And / or, the mechanical stripping method includes: obtaining a two-dimensional ferromagnetic material sheet from a bulk single crystal using a polymer stripping medium with controllable adhesion properties, and then aligning the polymer stripping medium with the two-dimensional ferromagnetic material sheet with a prefabricated electrode on a substrate (110) and separating the polymer stripping medium by slow contact and heating or dissolving.
10. The method for fabricating a storage device based on two-dimensional ferromagnetic intrinsic temperature-controlled magnetization characteristics according to claim 9, characterized in that, The polymer stripping medium is selected from at least one of polydimethylsiloxane, polycarbonate, polymethyl methacrylate, ethylene-vinyl acetate copolymer, polydimethylsiloxane modified material, polyolefin elastomer, polyvinyl alcohol, and polyethylene oxide.
Citation Information
Patent Citations
Two-dimensional magnetic material device and preparation method and regulation and control method thereof
CN119562753A
One transistor-type nonvolatile memory device and method for manufacturing the same
KR1020160011741A